Pengaruh Kontrol Diri, Stres Kerja Terhadap Cyberloafing Dalam Meningkatkan Kinerja Pegawai Dinas Ketahanan Pangan Dan Pertanian Kab Jepara - Zidan Faishol Basri; Ratih Hesty Utami P; Rauly Sijabat (Jurnal of Management and Social Sciences, 2024)
This study aims to determine the effect of self-control, work stress on cayberloafing in improving the performance of employees of the Food Security and Agriculture Office of Jepara Regency. The population of researchers is all civil servants at the Food Security and Agriculture Office of Jepara Regency as many as 100 people, in addition to the head of service, the sample that has been determined in this study is civil servants at the Food Security and Agriculture Office of Jepara Regency. Determination of the sample size using the Non Probability Sampling method with saturated sample technique. Data analysis in this study used the SmartPLS version 3 program. The data analysis technique used the Structural Equation Modeling (SEM) equation model. The results of the analysis and discussion show that self-control has a negative effect on cyberloafing, work stress has a positive and significant effect on cyberloafing, cyberloafing behavior has a negative effect on performance, self-control behavior has a positive and significant effect on performance, work stress has a negative effect on performance, self-control has a positive effect on Employee Performance through Cyberloafing, work stress has a negative effect on Employee Performance through Cyberloafing in Employees of the Food Security and Agriculture Office of Jepara Regency.